Phosphorylated neurofilament heavy chain in cerebrospinal fluid and plasma as a Nusinersen treatment response marker in childhood-onset SMA individuals from Serbia - Brkušanin, Miloš; Kosać, Ana; Branković-Srećković, Vesna; Jovanović, Kristina; Perić, Stojan; Karanović, Jelena; Matijašević Joković, Suzana; Garai, Nemanja; Pešović, Jovan; Nikolić, Dimitrije; Stević, Zorica; Brajušković, Goran; et al. (Frontiers in Neurology, 2024)
Introduction Biomarkers capable of reflecting disease onset and short- and long-term therapeutic effects in individuals with spinal muscular atrophy (SMA) are still an unmet need and phosphorylated neurofilament heavy chain (pNF-H) holds significant promise. Methods We conducted a longitudinal prospective study to evaluate pNF-H levels in the cerebrospinal fluid (CSF) and plasma of 29 individuals with childhood-onset SMA treated with Nuinersen (SMA type 1: n = 6, 2: n = 17, 3: n = 6). pNF-H levels before and during treatment were compared with the levels of controls (n = 22), patients with Duchenne muscular dystrophy (n = 17), myotonic dystrophy type 1 (n = 11), untreated SMA individuals with chronic type 3 disease (n = 8), and children with presymptomatic SMA (n = 3). Results SMA type 1 showed the highest mean CSF pNF-H levels before treatment initiation. All Nusinersen-treated individuals (types 1, 2, and 3) showed significantly elevated mean baseline CSF pNF-H compared to controls, which inversely correlated with age at disease onset, age at first dose, disease duration and the initial CHOP INTEND result (SMA type 1 and 2). During 22 months of treatment, CSF pNF-H levels declined during loading doses, stabilizing at reduced levels from the initial maintenance dose in all individuals. Baseline plasma pNF-H levels in type 1 and 2 SMA were significantly increased compared to other cohorts and decreased notably in type 1 after 2 months of treatment and type 2 after 14 months. Conversely, SMA type 3, characterized by lower baseline pNF-H levels, did not show significant fluctuations in plasma pNF-H levels after 14 months of treatment. Conclusion Our findings suggest that CSF pNF-H levels in untreated SMA individuals are significantly higher than in controls and that monitoring of CSF pNF-H levels may serve as an indicator of rapid short-term treatment response in childhood-onset SMA individuals, irrespective of the subtype of the disease, while also suggesting its potential for assessing long-term suppression of neurodegeneration. Plasma pNF-H may serve as an appropriate outcome measure for disease progression and/or response to treatment in types 1 and 2 but not in type 3. Presymptomatic infants with SMA may show elevated pNF-H levels, confirming early neuronal degeneration.